Occurrence and risk of human infection and antimicrobial susceptibilities of escherichia coli isolates from beef sold for human consumption in Jos metropolis, Plateau state Nigeria, September 2018 – June 2019 - Yohanna Iliya; Jacob Kwada Paghi Kwaga; Grace Sabo Kia; Yakubu Gunya Dogonyaro Dashe; Godwin Ojonugwa Agada; Muhammad Shakir Balogun; Charles Michael Akatobi (Journal of Interventional Epidemiology and Public Health)
Introduction: Antimicrobial resistance poses a threat to infection management globally. We determined the prevalence and antimicrobial susceptibilities of Escherichia coli (E. coli) isolates from beef and assessed beef seller's practices and awareness of antimicrobial resistance (AMR) from Jos metropolis, Plateau State, Nigeria.